(untitled) (Analysis in Theory and Applications, 2023)
In this paper, we first introduce some new kinds of weighted amalgam spaces. Then we discuss the strong type and weak type estimates for a class of Calderόn–Zygmund type operators T_θ in these new weighted spaces. Furthermore, the strong type estimate and endpoint estimate of linear commutators [b, T_θ] formed by b and T_θ are established. Also we study related problems about two-weight, weak type inequalities for T_θ and [b, T_θ] in the weighted amalgam spaces and give some results.